Characterization of eucalyptus clones subject to wind damage - Zanuncio, Antonio Jose Vinha; Carvalho, Amélia Guimarães; Carneiro, Angelica de Cassia Oliveira; Valenzuela, Paulina; Gacitúa, William; Leite, Fernando Palha; Colodette, Jorge Luiz (Pesquisa Agropecuaria Brasileira, 2017)
Eucalyptus wood is the main source of raw material for pulp production in South America, but obstacles, such as damage by winds, can reduce its productivity. This work aimed to test a new methodology to assess the resistance of trees to wind damage and determine the characteristics that increase clone resistance to winds. Tree resistance to breakage, basic density, ultrastructure, anatomy, mechanical properties and growth stress of wood have been evaluated in seven Eucalyptus grandis × Eucalyptus urophylla clones, collected from a region with a high incidence of wind damage. The Pearson correlation coefficient between the tree resistance to breakage and the ratio between the area damaged by the winds and the total area planted was -0.839, showing the efficiency of the methodology adopted. Trees with a high basic density, cell wall fraction, modulus of elasticity of the middle lamella and fibers, fiber hardness, modulus of rupture, growth stress and low microfibril angle and height and width of the rays showed greater resistance to wind damage. Therefore, the selection of clones with these features may reduce the incidence of damage by winds in Eucalyptus plantations.